The Entry Mode Choice and Performance of European Small and Medium Sized Enterprises Investing in Emerging Markets - [Barreiro da Silva], [M.] (2016)
As a result of specific characteristics, the internationalisation process of small and medium sized enterprises (SMEs) differs from that of other companies and can imply higher risks. Therefore, strategic decisions such as the entry mode choice should be taken more cautiously in order to maximise firms’ performance abroad. This study aims to examine the entry mode decisions of SMEs and how the decision for the adequate entry mode impacts on firms’ performance when investing in emerging markets. Using a qualitative framework, the investigation is built upon a single case study of a Portuguese company investing in Nigeria. Analysing the strategic decisions taken during the internationalisation process and its outcomes, the research meets its purpose. The findings indicate that SMEs’ specific characteristics do not always constitute a disadvantage; the small ownership structure of these companies can facilitate the adaptation to foreign environments and contribute to a quicker reaction to the challenges faced. Additionally, the study observes that cultural distance is a significant determinant of entry mode choice when investing in emerging markets, as it defines the risk and uncertainty of the investment. The findings highlight that engaging in a joint venture arrangement with a local partner is associated with the reduction of SMEs’ liabilities, directly affecting the performance of the foreign affiliate. The research concludes that the joint venture entry mode has the power to improve the performance of the SME’s foreign affiliate.